Maintaining the Strength of Pancasila Amid the Flow of Globalization in Students of Universitas Negeri Medan - Yona Venelia Hutabarat; Naomy Elisabeth Tamba; Jessica Simanjuntak; Bunga Uara Tambunan; Jamaludin (PT FORMOSA CENDEKIA GLOBAL, 2023)
After Indonesia's independence in 1945, Pancasila sat as the national ideology which became a reference in the life of the Indonesian people. In this era of globalization, the position of Pancasila as the nation's ideology is indispensable as a barrier in sorting out foreign cultures and ideologies that enter Indonesia. Pancasila in the modern era is a contemporary reality which shows that challenges to Pancasila ideology, both now and in the future, have appeared on the surface. The fading values of Pancasila can also be seen from the decline in the sense of patriotism and rationalism in the Indonesian people, especially in the younger generations. Pancasila is the basis of the state and the thinking of the life of the Indonesian people in the nation and state and is used as a guide in establishing the Unitary State of the Republic of Indonesia.